Occupational and Take-home Lead Exposure Among Lead Oxide Manufacturing Employees, North Carolina, 2016. (November 2018) - Rinsky, Jessica L.; Higgins, Sheila; Angelon-Gaetz, Kim; Hogan, Doris; Lauffer, Pierre; Davies, Megan; Fleischauer, Aaron; Musolin, Kristin; Gibbins, John; MacFarquhar, Jennifer; Moore, Zack
Objective: In 2016, North Carolina blood lead level (BLL) surveillance activities identified elevated BLLs among 3 children exposed to take-home lead by household members employed at a lead oxide manufacturing facility. We characterized BLLs among employees and associated children and identified risk factors for occupational and take-home lead exposure. Methods: We reviewed BLL surveillance data for 2012-2016 to identify facility employees and associated children. We considered a BLL ≥5 μg/dL elevated for adults and children and compared adult BLLs with regulatory limits and recommended health-based thresholds. We also conducted an environmental investigation and interviewed current employees about exposure controls and cleanup procedures. Results: During 2012-2016, 5 children associated with facility employees had a confirmed BLL ≥5 μg/dL. Among 77 people employed during 2012-2016, median BLLs increased from 22 μg/dL (range, 4-45 μg/dL) in 2012 to 37 μg/dL (range, 16-54 μg/dL) in 2016. All employee BLLs were <60 μg/dL, the national regulatory threshold for immediate medical removal from lead exposure; however, 55 (71%) had a BLL ≥20 μg/dL, a recommended health-based threshold for removal from lead exposure. Because of inadequate controls in the facility, areas considered clean were visibly contaminated with lead dust. Employees reported bringing personal items to work and then into their cars and homes, resulting in take-home lead exposure. Conclusions: Integration of child and adult BLL surveillance activities identified an occupational source of lead exposure among workers and associated children. Our findings support recent recommendations that implementation of updated lead standards will support better control of lead in the workplace and prevent lead from being carried home.